Structural and functional trends indicate fishing pressure on marine fish assemblages. Issue 3 (19th March 2014) - Henriques, Sofia; Pais, Miguel P.; Vasconcelos, Rita P.; Murta, Alberto; Azevedo, Manuela; Costa, Maria J.; Cabral, Henrique N.; Blanchard, Julia
Summary Conservation science increasingly focuses on how ecosystem functioning is affected by anthropogenic pressures, which implies an understanding of the structural and functional changes in biological assemblages and requires indicators to detect such changes within a suitable time frame. A novel approach that combines the spatial analysis of fishing gradients (based on vessel monitoring system records) with distance‐based linear models was used to assess the response of several functional and structural metrics of fish assemblages to gradients of trawling, within four distinct habitat types. In addition, critical thresholds of trawling intensity were identified for the most sensitive metrics through piecewise regression models. Overall, total biomass and dominance (i.e. number of species that make up 90% of the total biomass) metrics as well as metrics representing vulnerable features (such as chondrichthyes, species with very low resilience and sedentary species) were shown to be sensitive to fishing. Our results suggest that decreasing trends in these indicators are likely to be associated with direct and indirect fishing effects acting synergistically on specific features of fish assemblages leading to its homogenization, with likely impacts on ecosystems resilience. Critical thresholds at high, medium and low fishing intensity levels were identified depending on the metric used to assess fishing impacts, suggesting that it is difficult to define a single global target for fishing management as it ultimately will depend on management and conservation objectives (e.g. maintenance of biomass vs. maintenance of structure and function). Synthesis and applications. A key goal of the applied approach was to provide short‐term indicators that are sensitive to gradients of trawling intensity and can be extrapolated to a broader geographical region. The identification of thresholds of fishing pressure that fish assemblages can withstand before ecosystem functioning is altered is key for the development of indicators as warning mechanisms, as well as to assess performance measures for management. Understanding responses to other pressure sources (e.g. pollution, dredging) requires further research, and combining an integrative functional traits approach with a wider range of pressures may help make this achievable.